Anterior cruciate ligament ganglion: case report - Pedrinelli, André; Castellana, Fabio Bonini; Fontes, Ricardo Bragança de Vasconcellos; Coelho, Rafael Ferreira; Menezes Fº, Luiz Álvaro de (São Paulo Medical Journal, 2002)
CONTEXT: A ganglion is a cystic formation close to joints or tendinous sheaths, frequently found in the wrist, foot or knee. Intra-articular ganglia of the knee are rare, and most of them are located in the anterior cruciate ligament. The clinical picture for these ganglia comprises pain and movement restrictions in the knee, causing significant impairment to the patient. Symptoms are non-specific, and anterior cruciate ligament ganglia are usually diagnosed through magnetic resonance imaging or arthroscopy. Not all ganglia diagnosed through magnetic resonance imaging need to undergo surgical treatment: only those that cause clinical signs and symptoms do. Surgical results are considered good or excellent in the vast majority of cases. CASE REPORT: A 29-year-old male presented with pain in the left knee during a marathon race. Physical examination revealed limitation in the maximum range of knee extension and pain in the posterior aspect of the left knee. Radiographs of the left knee were normal, but magnetic resonance imaging revealed a multi-lobed cystic structure adjacent to the anterior cruciate ligament, which resembled a ganglion cyst. The mass was removed through arthroscopy, and pathological examination revealed a synovial cyst. Patient recovery was excellent, and he resumed his usual training routine five months later.